Personalized Medicine: the impact of ferrofluids, clinical procedures, strategies, applications,challenges, current trends, and reseach opportunities. - Gizachew Diga Milki (Emerging Trends in Personalized Medicines, 2026)
Personalized medicine has shown progressive development and evolution in health care systems. It is considered as transformative emerging medicine encorporating advanced technologies including genomics, AI as thinking partner, and nanotechnology in a greater extent. The quest for painless injection, lesstoxicity, rapid cell separation, and gene sequencing make ferrofluid the focus of personalized medicine. Currently, magnetic nanoparicles and ferrofluides are becoming driving force of personalized medicine. However, contronlling and managing nanoscale toxicity of magnetic nanoparticles and ferrofluids is challenging due to several factors. Thus, diagnosizing the underlying problems related to nanotoxicity effects, synthesis procedures, and design of magnetic nanoparticles and ferrofluids is primary important. This research, therefore delves into assessment of nanoscale properties and functionality of magnetic nanoparticles and ferrofluids for efficient personalized medicine.To this end, unrevaling the potential role of green synthesis methods, magnetic nanoparticles, and ferrfluids as therapeutic agent, diagnostic, and targeted drug delivery is visualized. A strategies such a streamlined approach, pharmacologices, genometic & AI technologies, are proposed to resolve the major challenges encountered in accelerating the research and developments in personalized medicine. Moreovers, the research acces the current trends, emerging technologies, and research progress involving ferrofluids and development of personalized medicine is focused.
Keywords: Personalized medicine; emerging technologies; ferrofuilds; magnetic nanoparticles; streamlime approach